Anti-Japan : the politics of sentiment in postcolonial East Asia - Ching, Leo T. S., 1962- (Duke University Press, 2019)
Leo T.S. Ching traces the complex dynamics that shape persisting negative attitudes toward Japan throughout East Asia, showing how anti-Japanism stems from the failed efforts at decolonization and reconciliation, the U.S. military presence, and shifting geopolitical and economic conditions in the region.